2022
DOI: 10.3390/su14148437
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on the Environmental Impact of Our Lifestyles and on Environmental Concern

Abstract: Since the beginning of 2020, the worldwide COVID-19 pandemic made it necessary to change our lifestyles (e.g., restrictions on transport or travelling and forced telework). This has also changed the environmental impact of our lifestyles. To quantify that impact, we used surveys to calculate the Ecological Footprint (EF) and environmental concern of Belgian respondents in 2021 and compared this to the EF-situation in 2017, before COVID-19. We observed that the EF became significantly lower during the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…This study has confirmed the influence of environmental awareness (EC) on consumers’ sustainable purchase intention (ERPI) in Peru, Mexico, Colombia and Chile. This result is in line with previous studies [ 116 ], which point out that environmental awareness (EA) is an essential motivator for developing behavioral intention. Likewise, this result is contrasted with the findings of [ 59 ], in which the authors point out that environmental knowledge significantly and positively influences green purchasing intentions.…”
Section: Discussionsupporting
confidence: 93%
“…This study has confirmed the influence of environmental awareness (EC) on consumers’ sustainable purchase intention (ERPI) in Peru, Mexico, Colombia and Chile. This result is in line with previous studies [ 116 ], which point out that environmental awareness (EA) is an essential motivator for developing behavioral intention. Likewise, this result is contrasted with the findings of [ 59 ], in which the authors point out that environmental knowledge significantly and positively influences green purchasing intentions.…”
Section: Discussionsupporting
confidence: 93%
“…Third, our evidence indicates that COVID-19 determined Environmental Consciousness (EC) in Latin American countries. In line with previous studies, our results show that Environmental Consciousness (EC) is an essential motivator for developing behavioral intention [ 1 , 41 ]. It is important to note that the results show that the pandemic scenario positively influenced the relationship between Environmental Consciousness (EC) and Environmentally Responsible Purchase Intention (ERPI) in all countries and all generations, demonstrating that this worldwide crisis has generated an effect on consumers, which could demonstrate the starting point towards a transition that establishes environmentally friendly behaviors [ 5 , 75 ]…”
Section: Discussionsupporting
confidence: 92%
“…This explanatory model is composed of five independent variables that collectively explain a phenomenon related to the dependent variable, Environmental Responsibly Purchase intention [ 117 , 118 , 119 , 120 ]. The results show evidence that supports the hypothesis proposed in prior studies concerning COVID-19’s influence as a phenomenon that has affected the population regarding environmental issues in society [ 1 , 4 ]. In terms of research findings (see Table 7 ), our main theoretical contribution is that our evidence supports the idea that Attitude (ATT), Perceived Behavioral Control (PBC), and Environmental Consciousness (EC) would influence the Environmentally Responsible Purchase Intention (ERPI), which are discussed as follows.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By comparison with the initial debate about climate change, public opinion has progressively aligned with scientific consensus (Nisbet & Myers, 2007 ; Poushter & Huang, 2019 ), and levels of environmental concern remain generally high (Leiserowitz et al, 2022 ) even after the appearance of other global priorities like of COVID-19 pandemic (Brügger et al, 2021 ; Drews et al, 2022 ; Van Ootegem et al, 2022 ). However, while the environmental crisis and climate change, in particular, are global phenomena (Beck, 1992 , 2009 ; Crutzen, 2002 ; Giddens, 1990 ; Urry, 2011 ), studies of environmental concern at the individual level have traditionally focused on the so-called developed countries—mostly the USA and Western Europe (Chryst et al, 2018 ; Harring et al, 2011 ; Pisano & Lubell, 2017 ; Tranter & Booth, 2015 ; Tuitjer & Dirksmeier, 2021 ).…”
Section: Climate Change Awarenessmentioning
confidence: 99%